Adjuvant radiotherapy for stage i endometrial cancer: An updated cochrane systematic review and meta-analysis - Kong, A; Johnson, N; Kitchener, H; Lawrie, T (2012)
Background The role of adjuvant radiotherapy in stage I endometrial cancer has changed in recent years. This updated Cochrane systematic review aimed to reexamine the efficacy and toxicity of adjuvant radiotherapy vs no treatment in stage I endometrial cancer. Methods We searched various databases including The Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, and the Specialised Register of the Cochrane Gynaecological Cancer Review Group (CGCRG) for randomized controlled trials that met the predefined inclusion criteria. The primary outcome was overall survival (OS); secondary outcomes were endometrial cancer-specific survival, locoregional recurrence, distant recurrence, and toxicity. Hazard ratios (HRs) were estimated and pooled if possible; otherwise, dichotomous data were extracted. All statistical tests were two-sided. Results Of the eight included trials, seven trials (3628 women) compared external beam radiotherapy (EBRT) and no EBRT (or vaginal brachytherapy [VBT]), and one trial (645 women) compared VBT and no additional treatment. EBRT statistically significantly reduced locoregional recurrence compared with no EBRT (or VBT alone) (HR = 0.36, 95% confidence Interval [CI] = 0.25 to 0.52; P < .001), but this did not translate into an improvement in OS (HR = 0.99, 95% CI = 0.82 to 1.20; P = .95), endometrial cancer-specific survival (HR = 0.96, 95% CI = 0.72 to 1.28; P = .80), or distant recurrence rates (risk ratio = 1.04, 95% CI = 0.80 to 1.35; P = .77). EBRT was associated with an increased risk of severe acute toxicity, severe late toxicity, and reduced quality of life scores. © 2012 The Author 2012.